In vivo anti-biofilm and anti-bacterial non-leachable coating thermally polymerized on cylindrical catheter - Zhou, Chao (2018)
Catheters are indispensable tools of modern medicine, but catheter-associated infection is a significant clinical problem, even when stringent sterile protocols are observed. When the bacteria colonize catheter surfaces, they tend to form biofilms making them hard to treat with conventional antibiotics. Hence, there is a great need for inherently antifouling and antibacterial catheters that prevent bacterial colonization. This paper reports the preparation of nonleachable antibiofilm and antibacterial cationic film coatings directly polymerized from actual tubular silicone catheter surfaces via the technique of supplemental activator and reducing agent surface-initiated atom-transfer radical polymerization (SARA SI-ATRP). Three cross-linked cationic coatings containing (3-acrylamidopropyl) trimethylammonium chloride (AMPTMA) or quaternized polyethylenimine methacrylate (Q-PEI-MA) together with a cross-linker (polyethylene glycol dimethacrylate, PEGDMA) were tested. The in vivo antibacterial and antibiofilm effect of these nonleachable covalently linked coatings (using a mouse catheter model) can be tuned to achieve 1.95 log (98.88%) reduction and 1.26 log (94.51%) reduction of clinically relevant pathogenic bacteria (specifically with methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococcus faecalis (VRE)). Our good in vivo bactericidal killing results using the murine catheter-associated urinary tract infection (CAUTI) model show that SARA SI-ATRP grafting-from technique is a viable technique for making nonleachable antibiofilm coating even on "small" (0.30/0.64 mm inner/outer diameter) catheter.